NILAI-NILAI PENDIDIKAN DALAM ALQURAN SURAT AL-ALAQ - Handoko, Edi Saputra, Zulheddi (Pascasarjana UIN Sumatera Utara, 2018)
Abstract: This study aims to determine the values of education that written in the Qur’an Surah Al-Alaq,and also to find out the contribution of Surah Al-Alaq to the Values of Education itself. This research is alibrary research, the primary data sources derived from Tafsir al-Maraghi, Tafsir As-Sya’rawi, Tafsir IbnuKatsir and Tafsir Tarbawi. Secondary data derived from valid sources includes supporting books in research,The method used in completing this thesis is the content analysis method. The results of this thesis researchare, first to discuss about the values of education in Surah Al-Alaq : (1) the values in reading activity (2)scientific values of reading (3) the values of tauhid (4) the values of moral (5) ) the values of the Quran (6),the values of Writing, (7) the values of teaching (8), the values of worship (9), the values of taqwa. Second, thecontribution of Surah Al-Alaq’s to education consists of: (1) to develop the science (2), exclamation to tauhidmovement Third, relevations of Surah Al-Alaq to the valueof education consisting of: (1) Al-Qur’anbecomesa guideline in education, (2), Process of learning is one of the human’s Fitrah.Penelitian ini bertujuan untuk mengetahui Nilai-Nilai Pendidikan dalam Alquran Surat Al-Alaq, untuk mengetahuikontribusi surat Al-Alaq terhadap Nilai-Nilai Pendidikan. Penelitian ini adalah penelitian pustaka(LibraryReseach), sumber data berupa data primer meliputi Tafsir al-Maraghi, Tafsir As-Sya’rawi, Tafsir Ibnu Katsirdan Tafsir Tarbawi. Adapun data sekunder meliputi buku-buku pendukung dalam penelitian, Metode yangdigunakan dalam menyelesaikan tesis ini adalah metode analisis isi (Content Analysis). Adapun hasil penelitiantesis ini adalah, pertama, membahas mengenai Nilai-Nilai pendidikan dalam Surat Al-Alaq terdiri dari : (1),Nilai Gemar Membaca (2), Nilai Keilmuan (3), Nilai Ketauhidan (4), Nilai Akhlak (5), Nilai Alquran (6),Nilai Gemar Menulis, (7), Nilai Gemar Mengajar (8), Nilai Ibadah (9), Nilai Ketakwaan, Kedua, KontribusiSurat Al-Alaq terhadap pendidikan Terdiri dari : (1), Mengembangkan Keilmuan (2), Seruan Bertuhid, Ketiga,Relevasi Surat Al-Alaq Terhadap Nilai Pendidikan Terdiri dari (1), Alquran Menjadi Pedoman dalam Pendidikan,(2), Belajar merupakan Fitrah manusia dengan pendidikan.Kata unci: Nilai-nilai Pendidikan, Surat Al-Alaq